Carbon paper and preparation method and application thereof
By combining modified fiber materials and resin, carbon paper is prepared by using a multi-step process, which solves the problem of insufficient rigidity of existing carbon paper and realizes high flexibility and high strength carbon paper preparation, which is suitable for complex working conditions.
Patent Information
- Application Number
- CN202510084752.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-11
AI Technical Summary
Among the existing carbon paper preparation technology, carbon paper products are highly rigid and cannot take into account both flexibility and strength. They are prone to problems such as creases, cracks, and crushing when higher fluid pressure, higher shear force and locally higher mechanical pressure.
Modified polyacrylonitrile fibers, preoxidized fibers or carbon fibers are used as fiber materials, combined with benzoxazine resin, and carbon paper is prepared by needle puncture, hydrotonic, drying, oxidation, sizing, hot pressing and high-temperature treatment to form carbon paper with strong flexibility characteristics.
The prepared carbon paper has strong flexibility characteristics, high weight and high density, which can adapt to strict assembly environments, reduce material losses, improve utilization, and have stronger adaptability. It is suitable for high-pressure proton exchange membrane hydrogen electrolytic cells and other working conditions.
Smart Images

Figure CN119800763A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of proton exchange membranes, and in particular relates to carbon paper and a preparation method and application thereof. Background Art
[0002] The main components of a proton exchange membrane fuel cell include a proton exchange membrane, a catalyst layer, a gas diffusion layer, a bipolar plate, etc. The gas diffusion layer is generally made of carbon paper as the base material, and is formed into a diffusion layer component with hydrophobicity and a special pore structure through hydrophobic treatment and microporous layer coating. Due to its structure and mass transfer function, the gas diffusion layer must have good mass transfer characteristics, high-quality conductivity, and high strength. As the base material of the gas diffusion layer, the quality of the various properties of carbon paper determines the performance of the final gas diffusion layer.
[0003] The current mainstream carbon paper preparation process uses short-cut carbon fibers as raw materials, and forms a carbon paper precursor - carbon felt through a papermaking process. Then, the final carbon paper product is formed through sizing, hot pressing curing, high temperature treatment and other processes. Due to the presence of a large amount of resin carbon inside, the carbon paper produced is usually hard, rigid and lacks flexibility. There are obvious problems in dealing with high fluid pressure, high shear force and local high mechanical pressure. It is easy to have mechanical damage such as creases, cracks and breakage, which puts extremely high requirements on the assembly and use of carbon paper. Although the prior art proposes to use a non-woven fabric preparation process to manufacture carbon paper products, the prepared carbon paper products can maintain high flexibility to cope with complex mechanical stress environments and actual working conditions. However, this type of preparation method is not suitable for high-weight and high-density carbon paper products in practical applications. In the face of the working conditions of proton exchange membrane hydrogen production electrolyzers, especially high-pressure and high-intensity ones, the carbon paper products with lower weight and body density obtained by this type of preparation method cannot be adapted, and are prone to mechanical damage and component failure. Summary of the invention
[0004] The present application provides a carbon paper and a preparation method and application thereof, aiming to solve the problems existing in the existing carbon paper preparation technology, such as the carbon paper products having strong rigidity, being unable to take into account both flexibility and strength, and being prone to creases, cracks, and breakage under high fluid pressure, high shear force, and high local mechanical pressure.
[0005] The first aspect of the present application provides a carbon paper, wherein the surface density of the carbon paper is 150 g / m 2 -300g / m 2 The bulk density of the carbon paper is 0.4 g / cm 3 -1.2g / cm 3 .
[0006] The carbon paper described in the present application has a strong flexibility feature. Compared with the carbon paper material made by general process, it can better adapt to various harsh assembly environments, reduce material loss in the assembly process, improve utilization rate, save costs, and has stronger adaptability.
[0007] According to some embodiments of the carbon paper described in the present application, the carbon paper includes the following raw materials: fiber material and resin.
[0008] According to some embodiments of the carbon paper described in the present application, the fiber material includes one or more of modified polyacrylonitrile fiber, pre-oxidized fiber and carbon fiber.
[0009] According to some embodiments of the carbon paper described in the present application, the fiber length of the fiber material is 5-100 mm.
[0010] According to some embodiments of the carbon paper described herein, the carbon yield of the resin is 2%-20%.
[0011] According to some embodiments of the carbon paper described in the present application, the resin includes one or more of benzoxazine, styrene acrylic emulsion, polyvinyl alcohol, polyvinyl butyral, modified phenolic resin, modified epoxy resin and modified acrylic resin; further preferably, the resin is benzoxazine.
[0012] According to some embodiments of the carbon paper described in the present application, the mass ratio of the fiber material to the resin in the carbon paper is (10-100):1.
[0013] The second aspect of the present application provides a method for preparing the carbon paper according to the first aspect of the present application, comprising the following steps:
[0014] (1) preparing a fiber material into a stacked fiber web, and sequentially subjecting the fiber web to acupuncture, hydroentanglement, drying and oxidation treatment to obtain an oxidized fiber nonwoven fabric;
[0015] (2) The oxidized fiber nonwoven fabric is sizing treated with a resin slurry, and then dried, and then hot pressed and treated at high temperature in sequence to obtain the carbon paper.
[0016] According to some embodiments of the carbon paper preparation method described in the present application, in step (1), the hydroentanglement includes a single-pass hydroentanglement treatment and / or a double-pass hydroentanglement treatment.
[0017] According to some embodiments of the carbon paper preparation method described in the present application, the number of times of the hydroentanglement treatment is 1-8 times.
[0018] According to some embodiments of the carbon paper preparation method described in the present application, the number of times of hydroentanglement treatment is 2 times.
[0019] According to some embodiments of the carbon paper preparation method described in the present application, the water needle density of the first hydroentanglement treatment is 100-5000 nozzles per board, and the water pressure is 10-300 bar. The water needle density of the second hydroentanglement treatment is 5000-25000 nozzles per board, and the water pressure is 300-800 bar.
[0020] According to some embodiments of the carbon paper preparation method described in the present application, the temperature of the oxidation treatment is 180-350° C., and the time of the oxidation treatment is 1-20 hours.
[0021] According to some embodiments of the carbon paper preparation method described in the present application, in step (2), the resin slurry includes a resin and a solvent, and the solid content of the resin slurry is 20%-60%.
[0022] According to some embodiments of the carbon paper preparation method described in the present application, the viscosity of the resin slurry at 25° C. is 2-200 mPa·s.
[0023] According to some embodiments of the carbon paper preparation method described in the present application, the solvent includes one or more of water, ethanol, methanol, ether, chloroform, chloroform, dimethyl sulfoxide, tetrahydrofuran, etc.
[0024] According to some embodiments of the carbon paper preparation method described in the present application, the temperature of the hot pressing is 50-160° C., the pressure of the hot pressing is 0.1-1.5 MPa, and the time of the hot pressing is 1-20 min.
[0025] According to some embodiments of the carbon paper preparation method described in the present application, the high temperature treatment includes a first stage high temperature treatment and a second stage high temperature treatment;
[0026] The temperature of the first stage high temperature treatment is 800-1500°C, and the time of the first stage high temperature treatment is 4-20h;
[0027] The temperature of the second stage high temperature treatment is 1800-3000° C., and the time of the second stage high temperature treatment is 0.5-10 hours.
[0028] The third aspect of the present application provides a gas dispersion layer, comprising the carbon paper described in the first aspect of the present application or the carbon paper obtained by the preparation method described in the second aspect of the present application.
[0029] The fourth aspect of the present application provides an application of the gas dispersion layer described in the third aspect of the present application in a fuel cell or a hydrogen production electrolyzer. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is an electron microscope scanning image of the carbon paper described in Example 1 of the present application;
[0031] Figure 2 This is an electron microscope scanning image of the carbon paper described in Example 2 of the present application;
[0032] Figure 3 This is an electron microscope scanning image of the carbon paper described in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0033] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0034] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0035] The present invention provides a carbon paper having a surface density of 150 g / m 2 -300g / m 2 , for example 150g / m 2 , 180g / m 2 , 200g / m 2 , 220g / m 2 , 250g / m 2 , 280g / m 2 , 300g / m 2 The carbon paper has a bulk density of 0.4 g / cm 3 -1.2g / cm 3 , for example 0.4g / cm 3 , 0.6g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.2g / cm 3 wait.
[0036] The carbon paper described in the present application has a strong flexibility feature. Compared with the carbon paper material made by general process, it can better adapt to various harsh assembly environments, reduce material loss in the assembly process, improve utilization rate, save costs, and has stronger adaptability.
[0037] In some embodiments of the present application, the carbon paper includes the following raw materials, fiber material and resin.
[0038] In some embodiments of the present application, the fiber material includes one or more of modified polyacrylonitrile fiber, pre-oxidized fiber and carbon fiber. The raw materials used for the carbon paper prepared in the embodiment of the present invention can be modified polyacrylonitrile fiber or pre-oxidized fiber. Compared with carbon fiber, the cost of raw materials is saved by more than 60%, which has cost advantages, can realize continuous and large-scale production, and the conditions for technology transformation are mature. The modified polyacrylonitrile fiber used in the embodiment of the present application was purchased from Hainan Xinlong Nonwoven Co., Ltd.; the pre-oxidized fiber used in the embodiment of the present application was purchased from SGL Special Graphite (Shanghai) Co., Ltd.
[0039] In some embodiments of the present application, the fiber length of the fiber material is 5-100 mm, for example, 5 mm, 10 mm, 20 mm, 30 mm, 40 mm, 50 mm, 60 mm, 70 mm, 80 mm, 100 mm, etc.
[0040] In some embodiments of the present application, the carbon yield of the resin is 2%-20%, such as 2%, 5%, 8%, 10%, 12%, 16%, 20%, etc. A relatively low carbon yield can ensure that there is less residual resin carbon after the carbon paper is subjected to high temperature treatment. The resin carbon belongs to hard carbon, and less residual resin carbon can keep the carbon paper matrix more flexible to cope with the mechanical stress generated during assembly and use and under more severe working conditions.
[0041] In some embodiments of the present application, the resin includes one or more of benzoxazine, styrene acrylic emulsion, polyvinyl alcohol, polyvinyl butyral, modified phenolic resin, modified epoxy resin and modified acrylic resin. The modified phenolic resin, modified epoxy resin and modified acrylic resin described in the present application are all purchased from Jinan Shengquan Co., Ltd.
[0042] In some embodiments of the present application, the resin is benzoxazine. As some preferred implementation cases, the benzoxazine includes a modified benzoxazine resin.
[0043] In some embodiments of the present application, the mass ratio of the fiber material and the resin in the carbon paper is (10-100):1, for example 10:1, 20:1, 35:1, 50:1, 60:1, 70:1, 80:1, 100:1, etc. The resin used has strong adhesion. Under the condition of this addition amount, the thickness control effect can be achieved during the hot pressing process. At the same time, there is basically no resin carbon residue after high-temperature treatment, which can maintain the original flexibility of the substrate.
[0044] The present application also provides a method for preparing the carbon paper according to the first aspect of the present application, comprising the following steps:
[0045] (1) preparing a fiber material into a stacked fiber web, and sequentially subjecting the fiber web to acupuncture, hydroentanglement, drying and oxidation treatment to obtain an oxidized nonwoven fabric;
[0046] (2) The oxidized nonwoven fabric is sizing treated with a resin slurry, and then dried, and then hot pressed and treated at high temperature in sequence to obtain the carbon paper.
[0047] The carbon paper material prepared by the preparation method described in this application has higher flexibility characteristics compared to general carbon paper materials, and can take into account both a larger surface density design and higher strength, so that it can adapt to harsh assembly conditions and complex working environments (especially the high-pressure environment in the hydrogen production electrolyzer).
[0048] The preparation process of the oxidized non-woven fabric in the first step of the preparation method described in the present application can ensure that the carbon paper substrate has the flexible characteristics unique to non-woven fabrics. The sizing, hot pressing, high temperature and other treatments in the second step can ensure that the carbon paper has good thickness consistency, effective thickness control and a high degree of graphitization to meet the conductivity requirements required by the carbon paper material.
[0049] In some embodiments of the present application, the fiber material is combed by a carding machine to form a single-fiber fiber web, and then the fiber web formed after combing is stacked through a web laying process to form a fiber web with a target grammage.
[0050] In some embodiments of the present application, the carding machine may be one or more of a single-doffer, a double-doffer, a triple-doffer and a quadruple-doffer, and the web-forming method may also be a filament-forming web-forming method, an air-flow-forming method or the like.
[0051] In some embodiments of the present application, the web laying can be performed in a straight laying or cross laying manner. The laying manner affects the differences in the horizontal and vertical directions of the product. From the demand point of view, the isotropy of the carbon paper product should be improved, and the cross laying manner is preferred.
[0052] In some embodiments of the present application, the fiber web is subjected to a needle punching process to form a first-stage fiber nonwoven fabric.
[0053] In some embodiments of the present application, the acupuncture treatment includes single-pass and / or multi-pass acupuncture treatment. The number of acupuncture treatments is 1-10 times, preferably 3 times of progressive treatment. The first acupuncture treatment uses a thicker diameter needle, and the acupuncture density is 5-20 needles / cm 2 In the second and third acupuncture processes, the diameter of the needles used is reduced successively, and the acupuncture density is gradually increased. The acupuncture density of the second acupuncture is set at 20-40 needles / cm 2 The third needle density is set at 40-60 needles / cm 2This gradual treatment allows the fiber nonwoven to maintain better consistency at this stage.
[0054] In some embodiments of the present application, the needle-punched fiber nonwoven fabric is subjected to a hydroentanglement treatment to further reinforce the fiber web, improve the entanglement effect between the fibers, increase the density of the nonwoven fabric, and also make the product surface more delicate.
[0055] In some embodiments of the present application, the spunlace includes a single-pass spunlace treatment and / or a double-pass spunlace treatment; the number of spunlace treatments is 1-8 times, preferably, the number of spunlace treatments is 2 times; more preferably, the water needle density of the first spunlace treatment is 100-5000 nozzles per board, the water pressure is 10-300 bar, and the water needle density of the second spunlace treatment is 5000-25000 nozzles per board, the water pressure is 300-800 bar. The surface of the fiber nonwoven fabric after spunlace treatment is more delicate, soft in texture, and has a higher density and tensile strength.
[0056] In some embodiments of the present application, the drying may be carried out by methods such as infrared heating, air blowing, and negative pressure dehumidification.
[0057] In some embodiments of the present application, the oxidation treatment is carried out in an oxygen atmosphere, the oxidation treatment temperature is 180-350°C, for example, 180°C, 200°C, 250°C, 280°C, 300°C, 320°C, 350°C, etc., and the oxidation treatment time is 1-20h, for example, 1h, 5h, 8h, 9h, 12h, 16h, 20h, etc.
[0058] In some embodiments of the present application, the oxidized nonwoven fabric has a gram weight of 100-600 g / m 2 , preferably 300g / m 2 The above high-weight samples have a bulk density of 0.3-1.5g / cm 3 At this stage, the high-weight samples are generally thicker and less consistent, and require thickness control through back-end processing technology, while further improving the bulk density of the samples.
[0059] In some embodiments of the present application, the oxidized fiber nonwoven fabric is sizing treated by dipping, spraying or other processes, and the sizing uses a resin solution with a low carbon yield, which is composed of a resin and an organic solvent or a non-organic solvent.
[0060] In some embodiments of the present application, in step (2), the resin slurry includes a resin and a solvent, and the solid content of the resin slurry is 20%-60%, for example, 20%, 30%, 35%, 40%, 50%, 56%, 60%, etc.
[0061] In some embodiments of the present application, the viscosity of the resin slurry at 25°C is 2-200mPa·s, for example, 2mPa·s, 5mPa·s, 10mPa·s, 15mPa·s, 28mPa·s, 50mPa·s, 68mPa·s, 79mPa·s, 93mPa·s, 110mPa·s, 115mPa·s, 130mPa·s, 156mPa·s, 180mPa·s, 193mPa·s, 200mPa·s, etc.
[0062] In some embodiments of the present application, the solvent includes one or more of water, ethanol, methanol, ether, chloroform, chloroform, dimethyl sulfoxide, tetrahydrofuran, etc.
[0063] In some embodiments of the present application, the drying includes drying methods such as infrared heating, air blowing, and negative pressure dehumidification. After drying, the solvent in the non-woven fabric is completely removed, and the benzoxazine resin is distributed on the fiber surface and the connection between the fibers.
[0064] In some embodiments of the present application, the hot pressing includes flat plate hot pressing, single-roll or multi-roll pressing, isostatic pressing machine continuous hot pressing, etc., preferably flat plate hot pressing, the hot pressing temperature is 50-160°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 110°C, 120°C, 150°C, 160°C, etc., the hot pressing pressure is 0.1-1.5MPa, for example, 0.1MPa, 0.5MPa, 0.9MPa, 1.2MPa, 1.5MPa, etc., the pressure can be adjusted according to the sample state and actual thickness requirements, the hot pressing time is 1-20min, for example, 1min, 5min, 8min, 12min, 16min, 20min, etc.
[0065] If the hot pressing temperature is too low, the thickness control effect will be insufficient during the hot pressing process, the product cannot be effectively thinned, and cannot be shaped; if the hot pressing temperature is too high, it will cause the fibers to undergo a certain cyclization reaction, the fiber cross-sectional morphology will change, and the entanglement force between the fibers will decrease, resulting in a decrease in the strength of the final product.
[0066] The dried oxidized fiber nonwoven fabric is heat-pressed to control its thickness, and the resin in the oxidized fiber nonwoven fabric is completely cured to fix the shape of the oxidized fiber nonwoven fabric. The resin also acts as a binder at this stage, which greatly reduces the thickness of the nonwoven fabric and greatly increases its bulk density. During the hot pressing curing process, the curing shrinkage rate of the resin is close to 0. Therefore, after curing, the resin will not have a significant effect on the morphology and distribution of the fibers. Unlike other types of resins, the nonwoven fabric that has undergone the hot pressing curing process can still maintain excellent flexibility.
[0067] In some embodiments of the present application, the high temperature treatment includes a first stage high temperature treatment and a second stage high temperature treatment; the temperature of the first stage high temperature treatment is 800-1500°C, such as 800°C, 950°C, 1100°C, 1200°C, 1300°C, 1500°C, etc., and the time of the first stage high temperature treatment is 4-20h;
[0068] The temperature of the second stage high temperature treatment is 1800-3000°C, such as 1800°C, 1950°C, 2000°C, 2200°C, 2600°C, 2850°C, 3000°C, etc. The time of the second stage high temperature treatment is 0.5-10h. During the first stage high temperature treatment, the equipment needs to be equipped with a relatively complete exhaust gas treatment device. During the first stage high temperature treatment, the oxidized fibers will experience a large proportion of weight loss. After the second stage high temperature treatment, the flexible carbon paper material is prepared, the fibers in the carbon paper reach a high degree of graphitization, and have excellent conductivity. The thickness of the carbon paper also decreases slightly due to the weight loss during the high temperature treatment.
[0069] The embodiment of the present application also provides a gas dispersion layer, including the carbon paper described in the first aspect of the present application or the carbon paper prepared by the preparation method described in the second aspect of the present application. The gas dispersion layer described in the present application can be used as a gas diffusion layer substrate on the anode and cathode sides of a fuel cell and a gas diffusion layer substrate on the cathode side of a PEM hydrogen production electrolyzer, and can even be applied to a diffusion layer diaphragm of a liquid flow battery under the premise of a higher gram weight design, and has a wide range of uses and low cost.
[0070] In some embodiments of the present application, the gas dispersion layer is used in a fuel cell or a hydrogen production electrolyzer. Because there is usually an ultra-high fluid pressure in the cavity of a PEM hydrogen production electrolyzer, the materials of each component are required to be able to withstand extremely high assembly press-fit strength, and also be able to withstand extremely high fluid impact pressure. The high-weight, high-density flexible carbon paper described in the present application can withstand a cavity pressure of more than 8MPa, and will not break or collapse under higher press-fit strengths, and can adapt to the above-mentioned application conditions. In addition to this application field, the carbon paper material can be used in similar more complex and harsh working conditions. The carbon paper prepared in the present application has a high electrical conductivity due to its high-weight, high-density design direction, which can reduce impedance power consumption and improve battery efficiency in fuel cell applications.
[0071] The technical solution of the present application is further described below in conjunction with specific embodiments and drawings.
[0072] Example 1
[0073] A method for preparing carbon paper comprises the following steps:
[0074] (1) Pre-oxidized fibers with a fiber length of 50 mm are combed into a single-fiber fiber web by a double doffer carding machine, and then a layered fiber web is formed by cross-laying; the layered fiber web is subjected to a single-pass needling treatment, and the number of needling treatments is controlled to be 3 times. The first needling treatment uses a needle with a relatively large diameter, and the needling density is 10 needles / cm 2 In the second and third acupuncture processes, the diameter of the needles used was reduced successively, and the acupuncture density was gradually increased. The acupuncture density of the second acupuncture was set at 20 needles / cm 2 The third needle density is set to 40 needles / cm 2 After the needle punching is completed, a pre-oxidized fiber nonwoven fabric is formed;
[0075] The pre-oxidized fiber nonwoven fabric after needle punching was subjected to a single-pass hydroentanglement treatment to reinforce the fiber web. The number of hydroentanglement treatments was controlled to be 2 times. The water needle density of the first hydroentanglement treatment was 1000 nozzles per board and the water pressure was 100 bar. The water needle density of the second hydroentanglement treatment was 5000 nozzles per board and the water pressure was 300 bar.
[0076] The pre-oxidized fiber nonwoven fabric after spunlace was dried and oxidized in an oxygen atmosphere at a temperature of 200° C. for 5 h to obtain an oxidized fiber nonwoven fabric.
[0077] (2) The oxidized fiber nonwoven fabric is sizing treated with a resin slurry (the resin slurry includes a benzoxazine resin with a carbon yield of 5% and an ethanol solvent, the solid content of the resin slurry is 30%, and its viscosity at 25°C is 50 mPa·s) through a spraying process, and the sizing amount of the benzoxazine resin during the sizing process is 1% of the mass of the oxidized fiber nonwoven fabric sample.
[0078] The sizing oxidized fiber nonwoven fabric was dried by infrared heating and subjected to flat-plate hot pressing at a temperature of 100°C. The pressure of the hot pressing treatment was controlled to be 0.5 MPa, and the hot pressing was performed for 10 minutes under this condition.
[0079] The oxidized fiber nonwoven fabric after the heat pressing treatment is subjected to high temperature treatment, first at 1200° C. for 10 hours, and then at 2000° C. for 10 hours, to obtain the carbon paper.
[0080] Example 2
[0081] The only difference between the method for preparing carbon paper described in Example 2 and that in Example 1 is that the fiber material used in the method for preparing carbon paper described in Example 2 is modified polyacrylonitrile fiber, and the rest of the operations are the same as those in Example 1.
[0082] Example 3
[0083] The only difference between the method for preparing carbon paper described in Example 3 and that in Example 1 is that the resin used in the method for preparing carbon paper described in Example 3 is polyvinyl butyral, and the rest of the operations are the same as those in Example 1.
[0084] Example 4
[0085] The only difference between the method for preparing carbon paper described in Example 4 and that in Example 1 is that the sizing amount of benzoxazine resin in the sizing process of the method for preparing carbon paper described in Example 4 is 0.5% of the mass of the oxidized fiber nonwoven fabric sample.
[0086] Example 5
[0087] The only difference between the method for preparing carbon paper described in Example 5 and that in Example 1 is that the sizing amount of benzoxazine resin in the sizing process of the method for preparing carbon paper described in Example 5 is 5% of the mass of the oxidized fiber nonwoven fabric sample.
[0088] Example 6
[0089] The only difference between the method for preparing carbon paper described in Example 6 and that in Example 1 is that the sizing amount of benzoxazine resin in the sizing process of the method for preparing carbon paper described in Example 6 is 8% of the mass of the oxidized fiber nonwoven fabric sample.
[0090] Example 7
[0091] The only difference between the method for preparing carbon paper described in Example 7 and that in Example 1 is that the water pressure of the first hydroentanglement treatment in the method for preparing carbon paper described in Example 7 is 50 bar.
[0092] Example 8
[0093] The only difference between the method for preparing carbon paper described in Example 8 and that in Example 1 is that the water pressure of the first hydroentanglement treatment in the method for preparing carbon paper described in Example 8 is 200 bar.
[0094] Example 9
[0095] The only difference between the method for preparing carbon paper described in Example 9 and that in Example 1 is that the temperature of the hot pressing treatment in the method for preparing carbon paper described in Example 9 is 150°C.
[0096] Example 10
[0097] The only difference between the method for preparing carbon paper described in Example 10 and that in Example 1 is that the temperature of the hot pressing treatment in the method for preparing carbon paper described in Example 10 is 180°C.
[0098] Embodiment 11
[0099] The only difference between the method for preparing carbon paper described in Example 11 and that in Example 1 is that the high temperature treatment in the method for preparing carbon paper described in Example 11 is directly treating at a temperature of 2000° C. for 10 hours.
[0100] Comparative Example 1
[0101] The only difference between the preparation method of the carbon paper described in Comparative Example 1 and that of Example 1 is that phenolic resin is used instead of benzoxazine resin in the preparation process of the carbon paper described in Comparative Example 1.
[0102] The physical properties of the carbon papers described in Examples 1-11 and Comparative Example 1 of the present application were studied, and the results are shown in Table 1.
[0103] Table 1
[0104]
[0105]
[0106] It can be seen from Table 1 that by comparing and analyzing Examples 1-2, it can be concluded that under the same process conditions, the use of polyacrylonitrile fiber as raw material can achieve the same level of various parameters of the product as compared with the use of pre-oxidized fiber as raw material, but the use of pre-oxidized fiber as raw material can save the oxidation step of the fiber and reduce energy consumption;
[0107] Analysis of Examples 1-3 shows that after the sizing treatment with polyvinyl butyral resin having a higher carbon yield instead of benzoxazine resin, the flexibility and air permeability of the obtained carbon paper will decrease to a certain extent, so benzoxazine resin is preferred.
[0108] From the analysis of Examples 4-6, it can be concluded that when the amount of benzoxazine resin is adjusted, an amount of 0.5% will result in insufficient product thickness control, low bulk density, and reduced strength, so the amount of resin should not be too low; after the amount of resin is increased within a limited range, the thickness of the carbon paper product can be more effectively controlled, the bulk density is higher, the conductivity is better, and the impact on bending flexibility and air permeability is negligible;
[0109] Analysis of Example 1 and Examples 7-8 shows that the hydroentanglement pressure has a critical influence on the bulk density of the carbon paper product. A higher hydroentanglement pressure will make the fibers entangled more tightly, so that the carbon paper has extremely high strength and conductivity. The hydroentanglement treatment at 200 bar has a better effect than that at 100 bar and 50 bar.
[0110] From the analysis of Example 1 and Examples 9-10, it can be concluded that increasing the temperature during the hot pressing process will cause the strength of the carbon paper product to decrease to a certain extent, decreasing to 30N at 180°C, which cannot meet the product design requirements;
[0111] In Example 11, continuous high temperature treatment at 2000°C is directly used, which can slightly improve the strength and flexibility of the product;
[0112] Analysis of Example 1 and Comparative Example 1 shows that replacing benzoxazine resin with phenolic resin having a very high carbon residue rate will result in a large amount of resin carbon remaining in the sample, which significantly reduces the flexibility of carbon paper. Therefore, benzoxazine resin is preferred in this patent.
[0113] The electron microscope scanning images of the carbon paper described in Example 1, Example 2 and Comparative Example 1 of the present application are respectively as shown in FIG. Figure 1 , Figure 2 and Figure 3 shown.
[0114] from Figure 1-Figure 3 It can be seen that there are almost no particle residues on the surface and joints of the carbon paper fibers obtained by the preparation method of the present application, while a large amount of resin carbon remains on the fiber surface and between the fibers of the carbon paper described in Comparative Example 1. The large amount of such carbon residue is also the main reason for the lack of product flexibility.
[0115] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A carbon paper, characterized in that: The surface density of the carbon paper is 150 g / m 2 -300g / m 2 The bulk density of the carbon paper is 0.4 g / cm 3 -1.2g / cm 3 .
2. The carbon paper according to claim 1, characterized in that The raw materials include: fiber materials and resins; Preferably, the fiber material comprises one or more of modified polyacrylonitrile fiber, pre-oxidized fiber and carbon fiber; more preferably, the fiber length of the fiber material is 5-100 mm; Preferably, the carbon yield of the resin is 2%-20%; more preferably, the resin includes one or more of benzoxazine, styrene acrylic emulsion, polyvinyl alcohol, polyvinyl butyral, modified phenolic resin, modified epoxy resin and modified acrylic resin; further preferably, the resin is benzoxazine.
3. The carbon paper according to claim 2, characterized in that The mass ratio of the fiber material to the resin in the carbon paper is (10-100):
1.
4. The method for preparing carbon paper according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) preparing a fiber material into a stacked fiber web, and sequentially subjecting the fiber web to acupuncture, hydroentanglement, drying and oxidation treatment to obtain an oxidized fiber nonwoven fabric; (2) The oxidized fiber nonwoven fabric is sizing treated with a resin slurry, and then dried, and then hot pressed and treated at high temperature in sequence to obtain the carbon paper.
5. The method for preparing carbon paper according to claim 4, characterized in that: In step (1), the hydroentanglement includes a single-pass hydroentanglement treatment and / or a double-pass hydroentanglement treatment; And / or, the number of hydroentanglement treatments is 1-8 times, preferably, the number of hydroentanglement treatments is 2 times; more preferably, the water needle density of the first hydroentanglement treatment is 100-5000 nozzles per board, the water pressure is 10-300 bar, and the water needle density of the second hydroentanglement treatment is 5000-25000 nozzles per board, the water pressure is 300-800 bar; And / or, the temperature of the oxidation treatment is 180-350° C., and the time of the oxidation treatment is 1-20 h.
6. The method for preparing carbon paper according to claim 4, characterized in that: In step (2), the resin slurry comprises a resin and a solvent, and the solid content of the resin slurry is 20%-60%; and / or, the viscosity of the resin slurry at 25° C. is 2-200 mPa·s; Preferably, the solvent includes one or more of water, ethanol, methanol, ether, chloroform, chloroform, dimethyl sulfoxide, tetrahydrofuran and the like.
7. The method for preparing carbon paper according to claim 4, characterized in that: The temperature of the hot pressing is 50-160° C., the pressure of the hot pressing is 0.1-1.5 MPa, and the time of the hot pressing is 1-20 min.
8. The method for preparing carbon paper according to claim 4, characterized in that: The high temperature treatment includes a first stage high temperature treatment and a second stage high temperature treatment; The temperature of the first stage high temperature treatment is 800-1500°C, and the time of the first stage high temperature treatment is 4-20h; The temperature of the second stage high temperature treatment is 1800-3000° C., and the time of the second stage high temperature treatment is 0.5-10 hours.
9. A gas dispersion layer, characterized in that: The invention comprises the carbon paper according to any one of claims 1 to 3 or the carbon paper obtained by the preparation method according to any one of claims 4 to 8.
10. Use of the gas dispersion layer according to claim 9 in a fuel cell or a hydrogen production electrolyzer.
Citation Information
Cited By
Near-net forming method of composite structure heat-proof layer
CN121179756A